ВОЗРАСТНЫЕ АСПЕКТЫ СТРУКТУРНО-ФУНКЦИОНАЛЬНЫХ ИЗМЕНЕНИЙ АРТЕРИЙ У ЛИЦ С ДИСПЛАЗИЕЙ СОЕДИНИТЕЛЬНОЙ ТКАНИ - А. А. Семёнкин; Г. И. Нечаева; О. В. Дрокина; В. Н. Махрова; С. А. Калиничева; Л. А. Живилова; О. И. Чиндарёва (SINAPS LLC, 2013)
We studied dependences of structural and functional changes of the arteries in 232 patients with connective tissue dysplasia. The increase of indicators of arterial stiffness and endothelial function in young patients with connective tissue dysplasia. With age, those with connective tissue dysplasia remain higher values of arterial stiffness, compared with the control group, and endothelial function is greatly reduced. These results confirm the effect of connective tissue dysplasia in the structure and function of the arteries.